2020
DOI: 10.1101/2020.11.11.20223800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Use of Saliva as a Diagnostic Specimen for SARS CoV-2 Molecular Diagnostic Testing for Pediatric Patients

Abstract: BackgroundChildren are an important population to test for COVID-19 infection, particularly because they may shed the virus without displaying symptoms. Testing children for COVID-19 via sensitive molecular methods is important, although collecting nasopharyngeal (NP) specimens can be challenging. A less invasive mode of specimen collection that yields test results comparable to those from NP specimens would be beneficial to simplify sample collection.MethodsTo demonstrate that saliva is a suitable specimen fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…103 papers were retained and assessed for full-text eligibility and 89 papers were excluded as they did not include children (individuals aged <18 years). Out of the 14 papers [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which fulfilled our eligibility criteria, we requested additional accuracy data for 9 papers of which we obtained 5. The final 10 8,10-17,21 studies included in the meta-analysis comprised 5 studies for which data was received from authors and 5 studies where data was available in the original article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…103 papers were retained and assessed for full-text eligibility and 89 papers were excluded as they did not include children (individuals aged <18 years). Out of the 14 papers [8][9][10][11][12][13][14][15][16][17][18][19][20][21] which fulfilled our eligibility criteria, we requested additional accuracy data for 9 papers of which we obtained 5. The final 10 8,10-17,21 studies included in the meta-analysis comprised 5 studies for which data was received from authors and 5 studies where data was available in the original article.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining six studies included both asymptomatic and symptomatic patients, but only one study 17 provided stratified data based on symptom status. All of the studies utilised nasopharyngeal swabs collected by healthcare workers as the comparator test except for two studies 10,14 which included nasopharyngeal and/or oropharyngeal swabs. Different techniques for saliva collection were used: general spitting technique in 5 studies 8,11,12,15,21 , drooling method in one study 13 , posterior oropharyngeal spitting technique (by asking children to clear their throats thoroughly and collect saliva) in one study 17 and 3 studies did not report the saliva collection technique 10,14,16 .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus we were not able to test our approach in two key demographics: elderly individuals (>65 years of age) who are the most at risk for disease and school-aged children (<18 years of age) who critically need testing to help support in-person learning, though others have recently demonstrated that saliva is a suitable specimen for pediatric testing. 64 Moreover, including professional athletes in our trial of repeat SARS-CoV-2 screening may not be representative of the general population, and we will therefore continue to monitor any laboratories using SalivaDirect for asymptomatic screening.…”
Section: Discussionmentioning
confidence: 99%